Detection and analysis of triterpenic compounds in apple extracts. Issue 1 (1st January 2018) - Butkevičiūtė, Aurita; Liaudanskas, Mindaugas; Kviklys, Darius; Zymonė, Kristina; Raudonis, Raimondas; Viškelis, Jonas; Uselis, Norbertas; Janulis, Valdimaras
ABSTRACT: A new technique for the rapid detection and analysis of triterpenic compounds in apple extracts using HPLC was developed and validated. The main advantage of this technique is the short duration of the analysis – this makes this technique superior to others currently applied for the routine HPLC analysis of triterpenic compounds. The developed, optimized, and validated technique was used for the evaluation of triterpenic compounds in samples of different cultivars of apples, their peels, and flesh. In total, four triterpenic compounds were isolated and identified. Ursolic acid was the dominant compound in all the tested apple samples. The highest amounts of triterpenic compounds were detected in the peels of the 'Lodel' apple cultivar, and thus apples of this cultivar may be potentially useful for the isolation of individual compounds and the production of functional food and dietary supplements.